Stem-cell-specific endocytic degradation defects lead to intestinal dysplasia in Drosophila - Péter Nagy; Laura Kovács; Gyöngyvér O. Sándor; Gábor Juhász (The Company of Biologists, 2016)
UV radiation resistance-associated gene (UVRAG) is a tumor suppressor involved in autophagy, endocytosis and DNA damage repair, but how its loss contributes to colorectal cancer is poorly understood. Here, we show that UVRAG deficiency in Drosophila intestinal stem cells leads to uncontrolled proliferation and impaired differentiation without preventing autophagy. As a result, affected animals suffer from gut dysfunction and short lifespan. Dysplasia upon loss of UVRAG is characterized by the accumulation of endocytosed ligands and sustained activation of STAT and JNK signaling, and attenuation of these pathways suppresses stem cell hyperproliferation. Importantly, the inhibition of early (dynamin-dependent) or late (Rab7-dependent) steps of endocytosis in intestinal stem cells also induces hyperproliferation and dysplasia. Our data raise the possibility that endocytic, but not autophagic, defects contribute to UVRAG-deficient colorectal cancer development in humans.